Subacute calorie restriction and rapamycin discordantly alter mouse liver proteome homeostasis and reverse aging effects. Issue 4 (23rd March 2015) - Karunadharma, Pabalu P.; Basisty, Nathan; Dai, Dao‐Fu; Chiao, Ying A.; Quarles, Ellen K.; Hsieh, Edward J.; Crispin, David; Bielas, Jason H.; Ericson, Nolan G.; Beyer, Richard P.; MacKay, Vivian L.; MacCoss, Michael J.; et al.
Summary Calorie restriction (CR) and rapamycin (RP) extend lifespan and improve health across model organisms. Both treatments inhibit mammalian target of rapamycin (mTOR) signaling, a conserved longevity pathway and a key regulator of protein homeostasis, yet their effects on proteome homeostasis are relatively unknown. To comprehensively study the effects of aging, CR, and RP on protein homeostasis, we performed the first simultaneous measurement of mRNA translation, protein turnover, and abundance in livers of young (3 month) and old (25 month) mice subjected to 10‐week RP or 40% CR. Protein abundance and turnover were measured in vivo using 2H3–leucine heavy isotope labeling followed by LC‐MS/MS, and translation was assessed by polysome profiling. We observed 35–60% increased protein half‐lives after CR and 15% increased half‐lives after RP compared to age‐matched controls. Surprisingly, the effects of RP and CR on protein turnover and abundance differed greatly between canonical pathways, with opposite effects in mitochondrial (mt) dysfunction and eIF2 signaling pathways. CR most closely recapitulated the young phenotype in the top pathways. Polysome profiles indicated that CR reduced polysome loading while RP increased polysome loading in young and old mice, suggesting distinct mechanisms of reduced protein synthesis. CR and RP both attenuated protein oxidative damage. Our findings collectively suggest that CR and RP extend lifespan in part through the reduction of protein synthetic burden and damage and a concomitant increase in protein quality. However, these results challenge the notion that RP is a faithful CR mimetic and highlight mechanistic differences between the two interventions.